2019
DOI: 10.1136/vr.105465
|View full text |Cite
|
Sign up to set email alerts
|

Paratuberculosis in dairy goat flocks from southern Spain: risk factors associated with seroprevalence

Abstract: BackgroundParatuberculosis (PTB) is a chronic, enteric wasting disease of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP), with a worldwide distribution. Andalusia, located in southern Spain, is one of the European regions with the highest goat census and the highest milk production; however, current data on the prevalence of MAP in this species are not available.MethodsA cross-sectional study was performed to determine the seroprevalence and risk factors associated with PTB in dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
7
1
Order By: Relevance
“…The individual and herd seroprevalence found in goats in this study was much higher than that previously reported in sheep. However, the seroprevalence reported in the present study was lower than expected considering the recent results in Southern Spain (Andaluc ıa), which found 87.5% of the herds (n 5 42) and 22.5% of goats (n 5 551) as reactors in the ELISA test (Barrero-Dom ınguez et al, 2019).…”
Section: Discussioncontrasting
confidence: 85%
“…The individual and herd seroprevalence found in goats in this study was much higher than that previously reported in sheep. However, the seroprevalence reported in the present study was lower than expected considering the recent results in Southern Spain (Andaluc ıa), which found 87.5% of the herds (n 5 42) and 22.5% of goats (n 5 551) as reactors in the ELISA test (Barrero-Dom ınguez et al, 2019).…”
Section: Discussioncontrasting
confidence: 85%
“…The low seroprevalence of MAP (3/564; 0.5%; CI 95%: 0.1–1.5) found in Iberian ibex in our study (Tables 1 and 2) coincides with previous reports in Spain, both in this species (Astorga Márquez et al., 2014) and in red deer ( Cervus elaphus ) (Carta et al., 2012), but contrasts with the higher seropositivity observed in other wild ruminant species in this country (Balseiro, García Marín, Solano, Garrido, & Prieto, 2008; Boadella et al., 2010). A markedly high seroprevalence of MAP has been reported in the study area in livestock species, including the domestic goat (Barrero‐Domínguez et al., 2019). Our results suggest that it is unlikely that the Iberian ibex makes a significant contribution to the maintenance of Brucella spp.…”
Section: Resultsmentioning
confidence: 88%
“…Due to different study design, sampling frames and the uncertainty of the diagnostic tests, MAP prevalence among small ruminants is difficult to estimate [4]. A few studies describe several risk factors associated with MAP prevalence in small ruminants [5][6][7][8][9][10][11], but further research is needed to confirm their validity for the local small ruminant population.…”
Section: Introductionmentioning
confidence: 99%